2021
DOI: 10.1002/slct.202004230
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing High‐quality Graphene from Spent Anode Graphite and Further Functionalization Applying in ORR Electrocatalyst

Abstract: A novel green and low‐cost synthesis route converting spent graphite anode from lithium‐ion batteries (LIBs) into graphene nanosheets was reported for the first time. The impurities in spent graphite were eliminated by calcining and acidic leaching. Compared with the typical Hummers method, notable oxidation efficiency enhancement was observed through introducing a 5 : 1 mixed suspension of H2SO4 and H3PO4 with slightly increased KMnO4, then high‐quality graphene sheets were obtained through glucose, thermal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Besides, nitrogendoped graphene was synthesized with a simple chemical doping approach, which can be used as an oxygen reduction reaction catalyst in fuel cells. [47] Yu et al [55] reported that the Modified Hummers method could be effectively used for impurity removal from recovered graphite and simultaneous conversion of it into 2D graphene oxide. In another study, Schiavi et al [56] proposed simultaneous production of rGO and LiÀ Mn-rich cathode material from spent LIB waste.…”
Section: Chemical Methods For Graphene Oxide/graphene Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, nitrogendoped graphene was synthesized with a simple chemical doping approach, which can be used as an oxygen reduction reaction catalyst in fuel cells. [47] Yu et al [55] reported that the Modified Hummers method could be effectively used for impurity removal from recovered graphite and simultaneous conversion of it into 2D graphene oxide. In another study, Schiavi et al [56] proposed simultaneous production of rGO and LiÀ Mn-rich cathode material from spent LIB waste.…”
Section: Chemical Methods For Graphene Oxide/graphene Synthesismentioning
confidence: 99%
“…Unlike natural graphite, anode graphite has organic and metallic impurities; treating with N-methyl-2-pyrrolidone (NMP), ethanol, and diluted water can remove these impurities. [43] Ruan et al [47] reported thermal treatment (600 °C) to decompose binders and other organic pollutants followed by acidic leaching (H 2 SO 4 & HCL) to eliminate metallic impurities. Other studies mentioned using de-ionized water to remove the Liimpurity and heating with dimethylformamide (DMF) to dissolve the binder.…”
Section: Recovery Of Anode Graphite From Spent Libsmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 Ruan et al successfully synthesized high-quality graphene from spent anode graphite and further applied functionalization in carbon-based redox ORR electrocatalyst, which has better methanol resistance and stability. 22 …”
Section: Introductionmentioning
confidence: 99%